Slovenia: Fiscal Sovereignty in the Frame of European Semester - Bohinc, Rado (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter explores the similarities and differences of Slovenia’s public finance system in terms of its position as a Member State of the European Union (EU) and Economic and Monetary Union, thereby identifying the reasons for potentially differing viewpoints. The chapter focuses on sovereignty and the advantages and challenges of the EU as a supranational community in the field of economic policy, with special regard to aligning the objectives of the EU and those of its Member States. The Introduction outlines the European Semester and presents data on the state debt and budget deficit in Slovenia. The first section then presents the constitutional rules in public finance in the Republic of Slovenia and discusses the theory on the republic’s budgetary independence and fiscal sovereignty at the various levels of public finance. This discussion includes consideration of the question of fiscal sovereignty in the EU versus its Member States. Next, the constitutional guarantees for the preservation of the deficit and debt level, including the fiscal rule in the Constitution of the Republic of Slovenia, are explored. The second section presents the rules guaranteeing the preservation of the fiscal deficit and state debt and the role of the central budgetary procedure and its stages. First, the EU legal framework on fiscal and macroeconomic surveillance, as well as the Slovenian national fiscal legal framework, the fiscal rule, and the impact of central budgetary planning on maintaining a balanced budget, are considered. The procedure of adopting and implementing the budget and reporting and control audit are also discussed in this section. In the third section, new trends in national fiscal policy, sustainability, and its implications for fiscal policy are examined, in addition to the fiscal policy challenges caused by technological development, digitalisation, and the energy crisis. This section also tackles the topic of crisis management methods related to COVID-19 and the energy crisis.Keywords: state debt, budget deficit, fiscal policy, fiscal rule, macroeconomic surveillance, municipal finance, excessive indebtedness, macroeconomic balances, economic governance, European Semester